rehearsal/performance. ART GALLERY OF ONTARIO, TORONTO - Litvack, Chaya (Archivaria, 2015)
rehearsal/performance. AME HENDERSON. Mounted at the Art Gallery of Ontario, Toronto. 27 August, 10 and 24 September, 2 and 4–5 October 2014.